The Influence of Attitudes and Subjective Norms on Interest in Using Certified Seedlings in Smallholder Plantation (Case Study: Sei Tarolat Village Farmers) (Talenta Publisher, 2020)
The purpose of this study was to analyze farmers 'assumptions in the use of certified seedlings on oil palm and analyze efforts that could improve farmers' understanding of the use of certified seedlings. This study was conducted in Sei Tarolat Village, Bilah Hilir District, Labuhan Batu Utara Regency. The study was conducted for 61 days starting from March to April 2020. Sampling was done using a purposive technique with a sample of 100 respondents. The method chosen for data analysis was the SEM (Structural Equation Model) method which was operated using the SmartPLS 3.0 program. The results of this study could be concluded that attitudes can influence the interest in using certified seeds in Sei Tarolat Village, Bilah Hilir District, Labuhan Batu Utara Regency and subjective norms can also influence the interest in using certified seeds in Sei Tarolat Village, Bilah Hilir District, Labuhan Batu Utara Regency. Keywords: attitude, certified seedlings, interest, subjective norm